Generalized Quasilinearization for Nonlinear Three-Point Boundary Value Problems With Nonlocal Conditions - Ahmad, Bashir (Sarajevo Journal of Mathematics, 2024)
We apply the generalized quasilinearization technique to obtain a monotone sequence of iterates converging quadratically to the unique solution of a general second order nonlinear differential equation with nonlinear nonlocal mixed three-point boundary conditions. The convergence of order n (n2) of the sequence of iterates has also been established. 2000 Mathematics Subject Classification. 34B10, 34B15